2008
DOI: 10.1111/j.1537-2995.2007.01584.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus window‐phase infections: closing the window on hepatitis C virus

Abstract: Combined antigen and antibody testing provides a useful improvement on the sole reliance on antibody testing for detection of HCV infection; however, it remains less sensitive than NAT for detecting viremic donors and may be genotype susceptible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 21 publications
0
24
1
Order By: Relevance
“…The impact of HCV diversity on antigen‐antibody combination assay performance has not been evaluated with precision due to their recent availability. The current results are conflicting, because Tuke and colleagues 10 reported a lack of detection of genotype 3a by the Bio‐Rad assay, independent of viral load, in contrast to previous studies with the same assay 20,26 . Further investigations will be necessary to provide firm conclusions.…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…The impact of HCV diversity on antigen‐antibody combination assay performance has not been evaluated with precision due to their recent availability. The current results are conflicting, because Tuke and colleagues 10 reported a lack of detection of genotype 3a by the Bio‐Rad assay, independent of viral load, in contrast to previous studies with the same assay 20,26 . Further investigations will be necessary to provide firm conclusions.…”
contrasting
confidence: 57%
“…This group concluded that the new fully automated Prism assay demonstrated a significant reduction of the window period (mean, 4.1 days) in comparison with the PRISM HIV O Plus assay detecting only antibodies; this improvement can be attributed to the analytical sensitivity for HIV antigen detection (33 pg/mL, based on the French Afssaps reference panel) and to enhanced specificity (99.95%) and clinical sensitivity, including the capacity for detection of HIV antigen of several subtypes. The second study by Tuke and colleagues 10 reported sensitivity results of a new HCV antigen‐antibody EIA (Murex HCV antigen‐antibody, Abbott) in comparison with a second CE‐marked HCV combo assay (Monolisa HCV antigen‐antibody Ultra, Bio‐Rad, Hercules, CA). This work highlighted the improvement provided by a combination assay in comparison to antibody screening.…”
mentioning
confidence: 99%
“…While the window period is signifi cantly reduced with a combined Ag/Ab assay in HIV-infected patients and in drug users compared to a traditional anti-HCV assay (13,14), PCR remains the test of choice in these patients since combined HCV Ag/Ab assays remain less sensitive than PCR during the window period (Tuke 2008) (Laperche 2005). The probability of diagnosing an acute HCV infection during the window period in low-risk patients is low.…”
Section: Discussionmentioning
confidence: 98%
“…The addition of antibodies directed against HCV core antigen results in a shorter window phase compared to traditional anti-HCV antibody assays (4)(5)(6), making this assay a reasonable alternative when PCR cannot be used for reasons such as cost or emergency (4). In routine laboratory practice, the Monolisa Ultra assay could be used as a fi rst-line test in selected high-risk patients and for the confi rmation of screening test-positive sera.…”
Section: Introductionmentioning
confidence: 99%
“…Serological methods take advantage of the host organism's natural immune response to measure antibodies generated in response to infection. While commonly employed, these approaches are often limited by the time required for the infection to generate a measurable immune response, often requiring weeks to months to achieve (Cheng et al, 2009; Tuke et al, 2008). Another common approach to virus detection relies upon the detection of viral proteins, DNA, or RNA.…”
Section: Introductionmentioning
confidence: 99%